Hyperplastic goiter in sheep in the semi-arid region of Paraiba, Brazil: case report (Research, Society and Development, 2020)
The aim of this study was to describe the clinical and anatomopathological findings and serum concentrations of free triiodothyronine (T3) and thyroxine (T4) from an outbreak of iodine (I) deficiency in sheep in the semi-arid region of Brazil. The outbreak was observed in a property located in the municipality of Sousa, West of the State of Paraiba, a semi-arid zone of Northeast Brazil. The studied lot was composed of 14 animals, between 12 and 18 months old, male, and mixed breed. The animals presented an increase in volume in the proximal portion of the neck, ventral to the mandibular arch, of firm consistency, suggesting a goiter. Thyroid samples were collected from animals that presented gland hyperplasia. In addition, blood samples were collected for serum analysis of thyroid hormones. The clinical findings, macroscopic characteristics, and histological findings observed in these cases are identical to those described in the literature for acquired goiter and constitute evidence that allows the definitive diagnosis of this condition. The mean concentrations observed in animals were:  Free T3 (0.5±0.08 pmol/L) and Free T4 (10.93±2.88 pmol/L). Based on the epidemiological findings, clinical signs, anatomopathological lesions, and serum analysis of thyroid hormones, we can affirm the outbreak of acquired goiter occurred due to inadequacies in feeding and mineral supplementation of the animals. Thus, in order to prevent the appearance of this nutritional disorder, it is of utmost importance that animals are provided with a balanced mineral diet and supplementation, taking into account the needs of the species and antithyroid feed substances.